2017
DOI: 10.1016/j.dld.2017.01.141
|View full text |Cite
|
Sign up to set email alerts
|

Safety of treatments for inflammatory bowel disease: Clinical practice guidelines of the Italian Group for the Study of Inflammatory Bowel Disease (IG-IBD)

Abstract: Inflammatory bowel diseases are chronic conditions of unknown etiology, showing a growing incidence and prevalence in several countries, including Italy. Although the etiology of Crohn's disease and ulcerative colitis is unknown, due to the current knowledge regarding their pathogenesis, effective treatment strategies have been developed. Several guidelines are available regarding the efficacy and safety of available drug treatments for inflammatory bowel diseases. Nevertheless, national guidelines provide add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 422 publications
(440 reference statements)
0
22
1
7
Order By: Relevance
“…The pivotal GEMINI studies demonstrated both the efficacy and safety of vedolizumab in achieving clinical relevant endpoints in Crohn's disease patients who were either naïve to or had previously failed therapy with TNFα‐antagonists . Several additional reports have demonstrated safety and efficacy with vedolizumab, offering a promising alternative to the anti‐TNFα class of biologic therapy. Interestingly, despite the noted safety, the GEMINI studies suggest that patients with Crohn's disease, unlike ulcerative colitis, may have an increased number of infectious complications with taking vedolizumab …”
Section: Introductionmentioning
confidence: 99%
“…The pivotal GEMINI studies demonstrated both the efficacy and safety of vedolizumab in achieving clinical relevant endpoints in Crohn's disease patients who were either naïve to or had previously failed therapy with TNFα‐antagonists . Several additional reports have demonstrated safety and efficacy with vedolizumab, offering a promising alternative to the anti‐TNFα class of biologic therapy. Interestingly, despite the noted safety, the GEMINI studies suggest that patients with Crohn's disease, unlike ulcerative colitis, may have an increased number of infectious complications with taking vedolizumab …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a wide range of pharmacological agents is used to manage UC, and given their diversity are associated with a broad range of adverse effects and safety concerns. In this regard, guidance for their use with a focus on safety has been developed based on current knowledge and clinical experience [45]. Conventional agents are associated with a number of safety concerns with the possibility of the involvement of multiple organ systems [45], and both conventional and biological agents may carry an additional concern of malignancy [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it has been shown that antibiotics may be used even to maintain IBD remission [ 89 ]. Among xenobiotics, rifaximin seems to influence remission in both CD and UC [ 90 ].…”
Section: The Role Of Rifaximin In Inflammatory Bowel Diseasesmentioning
confidence: 99%